PEDAGOGI CINTA: MEREKONSTRUKSI LANDASAN FILSAFAT PENDIDIKAN ISLAM MELALUI ANALISIS ISI DAN HERMENEUTIK TERHADAP TAFSIR AL-MISBAH KARYA M. QURAISH SHIHAB - Listiana, Heni; Akhwan Muhlis, Mokhammad; Afcarina Izzati, Najwa; Qathrun Nada, Zilfania; Muhlis, Achmad (Program Studi Pendidikan Agama Islam (PAI) Fakultas Tarbiyah dam Ilmu Keguruan Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2025)
This article examines the pedagogical crisis in contemporary Islamic education, which tends to be reductionist and oriented toward the transfer of knowledge alone, thereby neglecting the spiritual and ethical dimensions of students. In response to this issue, this study aims to formulate a theoretical framework called the Pedagogy of Love through a systematic interpretation of M. Quraish Shihab's Tafsir al-Misbah. This study uses a qualitative approach with a literature study method, while data analysis is carried out descriptively and analytically through a combination of content analysis and a hermeneutic approach. The results show that the Pedagogy of Love rests on three main pillars, namely: (1) the axiology of rahmah as a spiritual foundation manifested in exemplary behavior (uswah ḥasanah); (2) dialogical-humanistic learning as a pedagogical approach that honors the minds and hearts of students; and (3) an integrative curriculum that synergizes naqli and 'aqli knowledge. These findings confirm that the Pedagogy of Love is a transformative solution in shaping individuals who are not only intellectually superior, but also emotionally and spiritually mature, so that they are able to realize the ideal of insān kāmil, which is oriented towards the value of raḥmatan lil-‘ālamīn